U-Pb (ID-TIMS) zircon ages on pyroclastic events from Balcarce Formation, Tandilia System, Argentina: unreworked or reworked origin? - Cingolani, Carlos Alberto (2010)
In eastern Argentina the southernmost outcrops of the Río de la Plata cratonic region are exposed in the Tandilia System in the central part of the Buenos Aires province. The evolution of Tandilia comprises mainly a juvenile igneous-metamorphic Paleoproterozoic (2.2 to 2.1 Ga) basement named Buenos Aires Complex. After a long paleoweathering process the Sierras Bayas Group (c. 185 m thick) is a record of the first Neoproterozoic sedimentary unit (siliciclastic, dolostones, shales, limestones), covered by the Cerro Negro Formation (c.150- 400 m thick, siliciclastics) and assigned to the Upper Neoproterozoic (both were firstly called “La Tinta Group”). The final sedimentary transgression at the Early Paleozoic is the Balcarce Formation (c. 90-450 m thick) (Iñiguez et al., 1989) reflecting an independent marine basin evolution in a passive margin setting. It is important to mention that pyroclastic levels were recognized in Tandilia System by Cuomo et al. (1983) from boreholes (Olavarría region) and Dristas and Frisicale (1987, 2003) in outcrops for the Cerro del Corral, Sierras de la Tigra and Los Barrientos areas. Also there are several evidence (kaolinite clay deposits, quartz crystals, alunite and iron-rich levels) originated by subsequent hydrothermal activity (Dristas and Frisicale, 2003; Dristas and Martínez, 2003). These authors described an alteration of original fall out pyroclastic material related to mafic rocks at Cerro del Corral area in the sedimentary cover, showing a kaolinite and rutile-anatase assemblage from low-temperature process. Other deposits involving mainly reworked pyroclastic material were also recognized along the Tandilia System. The main purpose of this work is to present U-Pb zircon ages by ID-TIMS methodology, on samples taken from pyroclastic levels outcropped in Cerro del Corral area and discuss the implications on two lines: the study zircons helps to constrain the age of the Balcarce Fm or represent reworking material?